2021
DOI: 10.18632/aging.202353
|View full text |Cite
|
Sign up to set email alerts
|

Cell lineage-specific methylome and genome alterations in gout

Abstract: In this study, we examined data from 69 gout patients and 1,455 non-gout controls using a MethylationEPIC BeadChip assay and Illumina HiSeq platform to identify lineage-specific epigenetic alterations and associated genetic factors that contributed to gouty inflammation. Cell lineage-specific differentially methylated sites were identified using CellDMC after adjusting for sex, age, alcohol drinking, smoking status, and smoking history (total pack-years). Different cell lineages displayed distinct differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Additionally, the role of DNA methylation in gout was demonstrated through the discovery of a variant (rs2228611) in the DNA MethylTransferase 1 (DNMT1) gene whose presence is statistically increased in gout patients compared to controls (9). In line with this information, an innovative multi-OMICs study, in which the cell-specific methylome was compared between gout patients and controls, revealed that many differentially methylated gene regulatory genomic sites were associated with IL-1b expression in monocytes (55).…”
Section: Genetics and Epigenetics Of Goutmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, the role of DNA methylation in gout was demonstrated through the discovery of a variant (rs2228611) in the DNA MethylTransferase 1 (DNMT1) gene whose presence is statistically increased in gout patients compared to controls (9). In line with this information, an innovative multi-OMICs study, in which the cell-specific methylome was compared between gout patients and controls, revealed that many differentially methylated gene regulatory genomic sites were associated with IL-1b expression in monocytes (55).…”
Section: Genetics and Epigenetics Of Goutmentioning
confidence: 95%
“…Because epigenetics has now been identified as an important player in gouty arthritis, we thought to re-evaluate the impact of diet in light of nutrient-derived epigenetic modifiers. As described in the previous section, a significant number of epigenetic factors potentially affect gout onset and can contribute to further inflammation events worsening the symptoms (9,55). Among such factors influencing epigenetic changes are multiple compounds (listed in Table 1) that are commonly found in one's diet.…”
Section: Diet-derived Epigenetic Modifiersmentioning
confidence: 99%
“…Many genes possess hormone response elements in the region of their target genes, which can interfere with the transcription of target genes. The expression of DNA methylation is also under sex hormones (estrogens and androgens) control [21]. Hormonal and genetic factors have also been shown to play a relevant role in explaining these differences in CKD, as demonstrated by several experimental studies, showing an overall protective role for estrogens and progesterone [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that collagen-vascular diseases and autoimmune disorders affect females three to ten times more than males [27]. Environmental stressors-induced epigenetic alteration such as chemical exposures, drugs, and infections during pregnancy, ureter-placental hypoxia, and maternal undernutrition may lead to prematurity and LBW infants and the risk of long-term hypertension and metabolic syndrome leading to the development of CKD, in children and adults [14,15,20,21].…”
Section: Sex Differences In Susceptibility To Ckdmentioning
confidence: 99%
“…BIRC2 (Baculoviral IAP Repeat Containing 2) encodes a member of the inhibitors of apoptosis (IAP) family of proteins. BIRC2 expression is downregulated by promoter hypermethylation ( 49 , 50 ), which was also associated with increased IL-1β production ( 49 , 51 ). Similarly, hypermethylation of the SIRT1 gene (encoding the Sirtuin 1, a deacetylase whose downregulation has been found in many disease conditions) correlates with lower transcript levels and with an increased risk of inflammatory and metabolic diseases ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%